Implementation of p-q theory on unified power flow controller - Hassan, Haryani (2014)
The Flexible AC Transmission System (FACTS) became popular since it was introduced by Hingorani in the late 1988. It can be considered as the best solution to transfer higher energy without building a new transmission line. This research focuses on the design of Unified Power Flow Controller (UPFC) which are one of the best FACTS types controller. UPFC is the combination of two types of FACTS controller names Static Synchronous Compensator (STATCOM) and Static Synchronous Series Compensator (SSSC), that can be used to control either selectively or simultaneously all the three parameters (i.e. voltage, impedance and phase angle) to influence the power flow in the existing transmission line. The purpose of this research is to design the UPFC using the Matlab Simulink software and implementing the well known p-q Theory as a control strategy. The analysis of the UPFC based on p-q Theory together with the implementation of Proportional Integral (PI) controller are combined to be a controller of Pulse Width Modulation (PWM) H-bridge for both Statcom and SSSC circuit. The UPFC system in this research was automatic voltage control mode and automatic power (real and reactive) flow control without any intervention on both sending and receiving end voltage magnitude and angle. From the simulation results, it shows that the p-q Theory control strategy can effectively and promptly tracking the reference power given in an existing transmission line.